If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + x = 28 + -1x Solving 13 + x = 28 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 13 + x + x = 28 + -1x + x Combine like terms: x + x = 2x 13 + 2x = 28 + -1x + x Combine like terms: -1x + x = 0 13 + 2x = 28 + 0 13 + 2x = 28 Add '-13' to each side of the equation. 13 + -13 + 2x = 28 + -13 Combine like terms: 13 + -13 = 0 0 + 2x = 28 + -13 2x = 28 + -13 Combine like terms: 28 + -13 = 15 2x = 15 Divide each side by '2'. x = 7.5 Simplifying x = 7.5
| m/3-3=-5 | | k^2-18k+77=-3 | | a/6+12=18 | | a^2+8a-57=-9 | | 1/3b-4 | | 95+.75=116 | | lnx+x=0 | | 1-3/6x=9/5 | | 5x-4=13x+20 | | 4cos-3sec=0 | | 5x-45=13x+20 | | -[-2(-1+m)]=-3(-1+m) | | 225=120^2/s | | 9/x-2=5/x^2 | | 7n+2=24 | | 276=115^2/x | | 5/(3p)+2/3=(5+p)/(2p) | | N=w(1+QD) | | Not=w(1+QD) | | f(x)=4x^2+16x+2 | | 96-94y=0 | | 14n+12=5n-6 | | 33-2(7r+9)=-9-6r | | D=w(1+Qn) | | 33-3(7r+9)=-9-6r | | x^3-7x^2+2x-14= | | 9x-y-3=0 | | 3a-15=42 | | -16m^2+25=0 | | f(6)=36+1.531 | | f(6)=36+.1531 | | 2n+6=17 |